E-221 Transulnar arterial access for diagnostic cerebral angiography and neurovascular intervention. (4th August 2020) - Mattay, R; Cox, M; Ramchand, P; Sedora-Roman, N; Pukenas, B; Kung, D; Hurst, R; Choudhri, O
Abstract : Purpose: Supported by longstanding Class I evidence from the cardiology literature showing the safety of transradial artery access for coronary angiography (Choe et al ., 2016), an increasing number of neurointerventionalists have adopted the transradial approach for diagnostic cerebral angiography (Almallouhi et al ., 2020). A recent study specifically showed the noninferiority of transradial arterial access compared with the transfemoral approach for cerebral angiography (Stone et al ., 2020). As the transradial approach becomes more widely adopted, a few important caveats have become apparent that may preclude safe transradial arterial access (namely variant anatomy, vasospasm, or radial artery occlusion). In such cases, a transfemoral or transulnar approach may be the most feasible route for arterial access. The purpose of study was to document the feasibility and safety of ulnar artery access for both diagnostic cerebral angiography and neurointerventional cases. Materials and Methods: A retrospective review of a local institutional database at a high-volume neurovascular center was performed. Consecutive diagnostic and interventional neurovascular cases completed solely via ulnar artery access over a 12-month period were reviewed and analyzed. Data including type of case (diagnostic or interventional), reason for choosing ulnar artery access, technical success for ulnar artery cannulation, successful case completion, and complications were recorded. Results: The ulnar artery was accessed for 12 distinct cases in 11 patients over a 12-month period. The mean age was 52.5 years ± 16 years, and 8 total were female. Of these 12 procedures, 8 were diagnostic cerebral angiograms and 4 were neurovascular interventions. The intervention cases included pipeline flow diversion of an unruptured paraclinoid aneurysm, Pulserider stenting and coiling of an unruptured basilar tip aneurysm, coil embolization of a ruptured posterior communicating artery, and pre-operative embolization of a left cerebellopontine angle tumor. All 8 diagnostic angiograms were performed using 5 Fr sheaths and all 4 interventions required 6 Fr sheaths. The right ulnar artery was accessed in 9 out of 12 cases (75%). In all 12 cases, the ulnar artery was chosen for cannulation after ultrasound examination of the ipsilateral radial artery proved unfavorable for the procedure in question. The reasons for choosing the ulnar artery over the ipsilateral radial artery were the following: radial artery spasm (1 case), inability to pass the wire (1 case), and the remainder due to a dominant ulnar artery (ulnar artery diameter > ipsilateral radial artery diameter). All procedures were successfully completed without a need for conversion to femoral arterial access. All sites of ulnar artery access were closed via an inflatable band closure device. There were no forearm hematomas, hand ischemia, or arm nerve damage in any of the 12 cases. Conclusion: Transradial arterial access has been shown to have a lower rate of access site complications when compared with the femoral approach. Our experience suggests that transulnar artery access may also be a feasible and safe alternative for diagnostic cerebral angiography and neurovascular intervention. Disclosures: R. Mattay: None. M. Cox: None. P. Ramchand: None. N. Sedora-Roman: None. B. Pukenas: None. D. Kung: None. R. Hurst: None. O. Choudhri: None.